Media Pembelajaran sebagai Support System dalam Mencapai Tujuan Pembelajaran - Shahibul Ardhi; Shodiqin (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This learning media aims to develop and improve the learning of elementary school students. This media is a development media that uses the meta analysis method. One of the problems of education is the minimum of media facilities and infrastructure, so that teachers are required to be creative in improving the quality of learning in the classroom, such as developing learning media in the classroom. Interesting learning media that can overcome student boredom in learning activities is game-based learning activities, such as the application of snake and ladder game media. Children in elementary school have a tendency to play. Fun and relaxed situations will help children to increase their interest in learning. The development of learning media in the form of a snake and ladder game has an impact on providing discourse on alternative teaching media for the elementary level. The use of this learning media is expected to improve the quality of learning activities at the elementary level